Serum adipokine and ghrelin levels in nonalcoholic steatohepatitis - Yalniz, Mehmet; Bahcecioglu, Ibrahim Halil; Ataseven, Huseyin; Ustundag, Bilal; Ilhan, Fulya; Poyrazoglu, Orhan K.; Erensoy, Ahmet (Hindawi Ltd, 2006)
Adipokines and ghrelin play role in insulin resistance, the key pathophysiological abnormality in patients with nonalcoholic fatty liver diseases. In the present study, relationship between nonalcoholic steatohepatitis (NASH) and serum adipokine and ghrelin levels was investigated. Thirty seven patients with biopsy-proven NASH and 25 age- and sex-matched controls were enrolled. Ten of NASH patients (27%) had diabetes mellitus (n=5) or impaired glucose tolerance (n=5). Body mass index (BMI) was less than 30 kg/m(2) in 67.6% of patients, while in the remaining 32.4% it was more than 30kg/m(2). Serum adiponectin, leptin, TNF alpha, and ghrelin were determined. Serum leptin (15.49 +/- 4.84 vs 10.31 +/- 2.53) and TNF-alpha (12.1 +/- 2.7 vs 10.31 +/- 2.56) levels were significantly higher in the NASH group compared to in the control group (P <.001 for each). Nevertheless, adiponectin (11.1 +/- 2.1 vs 17.3 +/- 2.8) and ghrelin (6.46 +/- 1.1 vs 7.8 +/- 1.1) levels were lower in the NASH group than in the control group (P <.001 for each). Serum levels of the adipokines and ghrelin, however, were comparable in the subgroups of patients regardless of whether BMI was < 30 or > 30 or glucose tolerance was impaired or not (P >.05). Additionally, neither adipokines nor ghrelin was correlated with histopathological grade and stage (P >.05). In conclusion; there is a significant relationship between NASH and adipokines and ghrelin independent from BMI and status of the glucose metabolism. These cytokines that appear to have role in the pathogenesis of NASH, however, do not have any effect upon the severity of the histopathology.
Keywords: Insulin-Resistance; Fatty Liver; Tnf-Alpha; Adiponectin; Adipocyte; Obesity; Nash; Association; Metabolism; Receptors